As observações de Jean-Baptiste Say sobre a escravidão - Rocha, Antonio Penalves (Estudos Avançados, 2000)
THERE are profound differences in the Jean-Baptiste Say's comments on slavery betwen the first and the fifth editions of his Treatise of Political Economy, i.e., in the five editions the book had during the author's life. The author's aim in of this work is to examine why there were these differences.